UNDERSTANDING THE ROLE OF TECHNOLOGY IN HEALTHCARE: COMMITMENT OR DEPENDENCE TOWARDS SUCCESS - Renu Misra, Ravichandran N (International Journal of Advanced Science and Technology, 2020)
Background: The dynamism of business environment is due to the increased contribution of a very famous terminology i.e. “Technology”. It has made its way possibly in every industry and so as the healthcare industry a long way back. Subsequently various modifications in processes, products, techniques, policies, employee’s competencies aiming towards organizational success have found their abode in the system of healthcare organizations. This increased adoption of technology in the progression of service delivery has raised the concern of technological overdependence. The study details the progression of technology in healthcare industry by focusing on the associated modifications leading to various developmental changes. The study also discusses the important concern of healthcare professional’s rising dependence on technology eventually sidelining the development of their competencies.